Davis' theory of erosion and reincarnation has a profound impact on the development of geography - Luo, Junzhe (Transactions on Social Science, Education and Humanities Research, 2024)
Davis's erosion theory had a profound influence on the development of geography. This theory proposes the periodic cycle process of geomorphic evolution, which provides a new perspective and research method for the field of geography. It promoted the development of geomorphology and provided geoers with new tools to understand the evolution of surface morphology. Moreover, the theory has inspired research from other branches of geography such as soscience, hydrology and ecology. Therefore, Davis's theory of erosion of reincarnation plays an important role in the development of geography.